2020
DOI: 10.1002/lt.25653
|View full text |Cite
|
Sign up to set email alerts
|

Improved National Results With Simultaneous Liver‐Kidney Transplantation Using Donation After Circulatory Death Donors

Abstract: Previous large registry studies have demonstrated inferior outcomes for simultaneous liver‐kidney transplantation (SLKT) recipients of grafts from donation after circulatory death (DCD) donors compared with those from donation after brain death (DBD) donors in the era from 2000 to 2010. Given the improving national results in liver transplantation alone using grafts from DCD donors, the present study aimed to investigate if results with DCD‐SLKT have improved in the modern era. Patients undergoing SLKT between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…These studies demonstrated inferior patient survival as well as inferior liver and kidney graft survival with DCD-SLK compared with DBD-SLK transplant. More recently, a study investigating SRTR data demonstrated that there has been a significant improvement in the results with DCD SLKs in the modern era [45]. In that study, patients undergoing DCD SLK in the Era 2011-2018 were able to achieve similar outcomes compared with matched patients undergoing DBD-SLK transplant, with no differences seen in patient, liver graft, or kidney graft survival.…”
Section: Recipient Selection and Importance Of Donor And Recipient Mamentioning
confidence: 97%
“…These studies demonstrated inferior patient survival as well as inferior liver and kidney graft survival with DCD-SLK compared with DBD-SLK transplant. More recently, a study investigating SRTR data demonstrated that there has been a significant improvement in the results with DCD SLKs in the modern era [45]. In that study, patients undergoing DCD SLK in the Era 2011-2018 were able to achieve similar outcomes compared with matched patients undergoing DBD-SLK transplant, with no differences seen in patient, liver graft, or kidney graft survival.…”
Section: Recipient Selection and Importance Of Donor And Recipient Mamentioning
confidence: 97%
“…Reported outcomes for solitary DCD kidney and liver allografts have demonstrated continuing improvement, however, data specific to DCD SLK transplants remains limited. 11,12,14,[16][17][18] To date, there have only been 2 single-center reports and 2 UNOS data analyses published on outcomes specific to DCD SLK (Table 5). 14,[16][17][18] LaMattina et al reported excellent outcomes (100% 1-year patient and graft survival) with DCD SLK in a small group of 5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…With growing experience, more recent studies have, however, consistently shown improving outcomes and increased organ utilization for both solitary DCD kidney and liver transplants. [9][10][11][12][13][14][15] The observed increase of nationally performed DCD SLK transplants have also been suggestive of improved outcomes, but, to date, there continues to be limited granular data on outcomes specific to this group. 14,16 As such, the aims of this study were to compare (1) patient and allograft survival rates,…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue, Croome et al used the UNOS Standard Analysis and Research File to compare the outcomes of DCD-SLKT between 2 eras: 2000-2010 (era 1) and 2011-2018 (era 2). (12) Improvements in DCD-SLKT patient, liver graft, and kidney graft survival rates were seen in era 2 compared with era 1. One should note that these recipients received high-quality organs based on mean donor age (32-33 years), mean kidney donor profile index (KDPI; 38%-40%), and mean donor warm ischemia times (17 minutes).…”
Section: See Article On Page 397mentioning
confidence: 98%
“…In the current issue, Croome et al used the UNOS Standard Analysis and Research File to compare the outcomes of DCD‐SLKT between 2 eras: 2000‐2010 (era 1) and 2011‐2018 (era 2) . Improvements in DCD‐SLKT patient, liver graft, and kidney graft survival rates were seen in era 2 compared with era 1.…”
mentioning
confidence: 99%